2004
DOI: 10.3354/ame037219
|View full text |Cite
|
Sign up to set email alerts
|

Benthic nutrient fluxes in euphotic sediments along shallow sub-tropical estuaries, northern New South Wales, Australia

Abstract: Diurnal benthic fluxes of dissolved inorganic and organic nitrogen (DIN and DON) and dinitrogen gas (N 2 ) were measured in euphotic sediments of 3 shallow sub-tropical Australian estuaries during 4 seasons. The estuaries included 2 impacted by sewage effluent (Brunswick and Simpsons estuaries) and 1 relatively pristine system (Sandon estuary). Sediments acted predominantly as net sinks of DIN throughout the year, except in the nutrient-enriched upper reaches of the Brunswick estuary, where large effluxes of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 85 publications
8
49
3
Order By: Relevance
“…Nutrient concentrations in the extracted interstitial water were measured using a TRAACS-800 autoanalyser. This method extracts both pore water nutrients and intracellular nutrients from the sediment microbiota (Lomstein et al 1990, Sayama 2001, Ferguson et al 2004.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrient concentrations in the extracted interstitial water were measured using a TRAACS-800 autoanalyser. This method extracts both pore water nutrients and intracellular nutrients from the sediment microbiota (Lomstein et al 1990, Sayama 2001, Ferguson et al 2004.…”
Section: Methodsmentioning
confidence: 99%
“…The freeze-lysable inorganic nutrient fraction measured in the sediment contains both the nutrients dissolved in the pore water and the intracellular nutrients released due to cell breakage (Lomstein et al 1990, Sayama 2001, Ferguson et al 2004). The intracellular pool has been shown to represent most of the freezelysable fraction in the upper layer of the sediment (0 to 2 mm), declining sharply with depth (Lomstein et al 1990, Sayama 2001.…”
Section: Accumulation Of Inorganic Nutrients In the Sedimentmentioning
confidence: 99%
“…The aerobic mineralization of planktonic organic matter can be expressed in the following equations: The flux of biogenic elements is expected to occur in the Redfield ratio, but interplay of several processes such as nitrification, denitrification, adsorption, desorption, and macrobenthic activities may cause deviation from the expected ratio (Koop et al, 1990;Cowan and Boynton, 1996;Giblin et al, 1997;Ferguson et al, 2004;Faganeli and Ogrinc, 2009) in coupled nitrification-denitrification (Jenkins and Kemp, 1984) and NH + 4 adsorption onto clay minerals (Rosenfeld, 1979;Mackin and Aller, 1984). Decrease in the NH 4 flux ratio during the October incubations (0.55-0.78) apparently would favor the growth of non-siliceous phytoplankton during the late monsoon.…”
Section: Stoichiometry Of Fluxesmentioning
confidence: 99%
“…Previous studies have shown that the production to respiration (P:R) ratio of the sediment is a useful metric of MPB activity and has a strong influence on the nutrient demand of the sediments (Rizzo et al 1996, Ferguson et al 2004b, Engelsen et al 2008. At P:R > 1, sediments tend to be a sink for nutrients as a consequence of MPB nutrient requirements exceeding the capacity of the sediments to supply nutrients, making MPB most likely nutrient-limited under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…At P:R < 1, sediments will be a source for nutrients, with the capacity of the sediments to supply nutrients exceeding the assimilative requirements of MPB, so that MPB are highly unlikely to become nutrient-limited. Furthermore, the sediment P:R ratio has also been shown to have a strong influence over benthic denitrification rates and the relative importance of organic nutrient fluxes, highlighting its strong influence over a range of microbial processes (Risgaard-Petersen 2003, Ferguson et al 2004b, Engelsen et al 2008.…”
Section: Introductionmentioning
confidence: 99%